Mechanical Design Criteria of a Six-D.o.F Retractor Equipped with an Interlock Mechanism for Locking and Releasing all Joints - Yukawa, Toshihiro; Sato, Hiroki; Takeda, Youichi; Sasaki, Jun (European Journal of Applied Sciences, 2025)
In this paper, we describe a new type of assist fixator (arm), which is a surgical instrument developed as an abdominal retractor during surgery. The developed fixator as the instrument can increase the efficiency of retraction function during surgery. As for the conventional retractor, the amount of rotation of the knob required for fixing and loosening was large, the number of the knob was many, and it took time to operate. To overcome these problems, we propose an assistance mechanism in which a six-D.o.F has high controllability at the end-effector. The whole mechanism of the assist arm consists of a serial four-link with three joints, and each joint is composed of a universal gear mechanism. The assist arm can maintain the posture and hold a part of a person's body on the operation table.